2011
DOI: 10.3382/ps.2010-01006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and combined Mycoplasma gallisepticum vaccinations on blood electrolytes and acid-base balance in commercial egg-laying hens

Abstract: A previous study from our laboratory on F-strain Mycoplasma gallisepticum-inoculated layers showed a significant increase in arterial partial pressure of oxygen (pO(2)), which is generally associated with an oxygen-dependent improvement in tissue oxygenation. The aim of this study was to determine whether a killed (bacterin) and live TS-11-strain M. gallisepticum (TS-11-MG) vaccine treatment combination could further enhance the arterial pO(2) levels in layer chickens. The experiment was conducted in 2 trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…The changes in pO 2 and pCO 2 , subsequent to the MG challenges imposed by Olanrewaju et al. (2009 , 2011) , were opposite to those noted in the present study. However, the responses reported in the previous and present studies are indicative of the ability of these various strains of MG to cause alterations in the blood gases of layers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The changes in pO 2 and pCO 2 , subsequent to the MG challenges imposed by Olanrewaju et al. (2009 , 2011) , were opposite to those noted in the present study. However, the responses reported in the previous and present studies are indicative of the ability of these various strains of MG to cause alterations in the blood gases of layers.…”
Section: Discussioncontrasting
confidence: 99%
“…(2009) reported that the eye drop inoculation of layer pullets with FMG caused the blood partial pressures of O 2 and CO 2 to be increased and decreased, respectively, at 9 woa. In a subsequent study by Olanrewaju et al. (2011) , it was also noted that when compared with MG-clean controls and those inoculated at 10 woa with a killed vaccine (bacterin) followed at 18 woa by live TS-11MG, the inoculation of layers with a live TS-11MG vaccine alone at 10 woa caused the partial pressures of O 2 to be increased and of CO 2 to be decreased in their blood at 56 woa.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations